Surgical Strategy for Squamous Cell Carcinoma of the External Auditory Canal: Management of Locally Advanced Cases with Skull Base Involvement - Goto, Seiya; Nishio, Naoki; Iwami, Kenichiro; Yoshida, Tadao; Maruo, Takashi; Mukoyama, Nobuaki; Tsuzuki, Hidenori; Yokoi, Sayaka; Wada, Akihisa; Hiramatsu, Mariko; Hayashi, Yuichiro; Kamei, Yuzuru; Fujii, Masazumi; Sone, Michihiko; Fujimoto, Yasushi (Journal of Neurological Surgery Part B: Skull Base, 2022)
Objective Surgical indications for advanced-stage squamous cell carcinoma (SCC) of the external auditory canal (EAC) are highly dependent on the skull base surgery team. The aim of this study was to evaluate the surgical outcomes in patients with SCC of the EAC and to clarify the surgical indication of far advanced cases using the T4 subclassification.Methods Patients with SCC of the EAC who underwent curative treatment from 2002 to 2021 at our hospital were retrospectively reviewed. Clinical and surgical results, including operative data, overall survival (OS), and disease-specific survival (DSS), were analyzed. To clarify the surgical indication for advanced-stage tumors, we proposed the T4 subclassification.Results In the 46 patients included in the study, 8 patients had T1 tumors, 10 had T2 tumor, 5 had T3 tumors, and 23 had T4 tumors. The 5-year DSS with T1, T2, T3, and T4 tumors were 100, 85.7, 100, and 61.7%, respectively. No prognostic impacts for margin status were found between the 5-year OS and DSS (p = 0.23 and 0.13, respectively). Patients with far-advanced-stage (T4b) tumors were significantly associated with shorter DSS than those with early-stage (T1/T2) and advanced-stage (T3/T4a) tumors (p = 0.007 and 0.03, respectively).Conclusion The present study focused on patients with SCC of the EAC at a university hospital over a period of 20 years, especially with skull base involvement, and a T4 subclassification was proposed. Complete tumor resection in an en bloc fashion could help achieve a good survival rate even in patients with locally advanced tumors.
Keywords: external auditory canal cancer; squamous cell carcinoma; surgical strategy; overall survival; disease-specific survival; T4 subclassification